Drying Characteristics of Osmosed Mango, Guava and Aonla - Kumar, P. Suresh; Sagar, V. R. (Journal of Agricultural Engineering, 2014)
Three fruits viz., mango, guava slices and aonla segments were osmo-dried under four different dying conditions viz., cabinet drier (CD), vacuum drier (VD), low temperature drier (LTD) and solar drier (SD). It was found that vacuum drying was superior to other mode of drying, as it retained better quality like acidity, ascorbic acid, and sugar. Further, drying rate, moisture ratio, drying ratio and rehydration ratio were also superior in vacuum drying. In addition, sensory score was higher in vacuum dried product, while the non enzymatic browning was least in vacuum dried product, and maximum in solar dried product.